Twenty-Four Million Words and Still Counting: The International Journal of the History of Sport, 1984–2020. Issue 17 (12th December 2019) - Vamplew, Wray
Abstract: The International Journal of the History of Sport began life in 1984 as the three issues per annum British Journal of Sports History but is now the world's premier sports history journal publishing 18 issues a year. This paper traces its development under the direction of four Managing Editors.